2023
DOI: 10.2991/978-2-494069-35-0_42
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy and Behavioral Bias of Individual Investors: Empirical Research in Indonesia

Abstract: Financial literacy and behavioural biases are critical factors that influence investment-decision making individual investors. This study aims to identify financial literacy relationships and behavioural biases (overconfidence, representativeness, and illusion of control) which can lead to irrational behaviour in investment decision making. The population in this research data is individual investors who are on Java. Based on the purposive sampling method, the sample was 83 respondents through a questionnaire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The studies on investment biases (Ahmad & Shah, 2020; Kumar & Goyal, 2016; Mittal, 2022), the influence of FL in reducing investment biases (Baker et al, 2019; Ozen & Ersoy, 2019; Rasool & Ullah, 2020; Wijayanto et al, 2023) are plenty. However, less attention has been paid to examining the impact of financial literacy level (FLL) on investment decisions in general (Saleem et al, 2023; Weixiang et al, 2022) and in the Indian context in particular.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on investment biases (Ahmad & Shah, 2020; Kumar & Goyal, 2016; Mittal, 2022), the influence of FL in reducing investment biases (Baker et al, 2019; Ozen & Ersoy, 2019; Rasool & Ullah, 2020; Wijayanto et al, 2023) are plenty. However, less attention has been paid to examining the impact of financial literacy level (FLL) on investment decisions in general (Saleem et al, 2023; Weixiang et al, 2022) and in the Indian context in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies (Ozen & Ersoy, 2019; Wijayanto et al, 2023) have shown that FL plays a substantial role in mitigating the biases inherent in individual investment decisions and financial decision‐making processes. Liu and Lu (2023) note that high levels of FL enhance the comprehension of risky financial products and information attention.…”
Section: Introductionmentioning
confidence: 99%